2020
DOI: 10.2105/ajph.2019.305364
|View full text |Cite
|
Sign up to set email alerts
|

Population Health Impact and Cost-Effectiveness of Community-Supported Agriculture Among Low-Income US Adults: A Microsimulation Analysis

Abstract: Objectives. To estimate the population-level effectiveness and cost-effectiveness of a subsidized community-supported agriculture (CSA) intervention in the United States. Methods. In 2019, we developed a microsimulation model from nationally representative demographic, biomedical, and dietary data (National Health and Nutrition Examination Survey, 2013–2016) and a community-based randomized trial (conducted in Massachusetts from 2017 to 2018). We modeled 2 interventions: unconditional cash transfer ($300/year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Both interventions demonstrated incremental cost-effectiveness ratios of <$100 000 per prevented DALY, with the cash transfer being more effective in the short term and the CSA being equally cost-effective in the long term, highlighting cost savings to society of −$191 100 per DALY averted (95% CI, −191 767 to −188 919) for the cash intervention and −$93 182 per DALY averted (95% CI, −93 707 to −92 503) for the CSA intervention. 132…”
Section: Nutritionmentioning
confidence: 99%
“…Both interventions demonstrated incremental cost-effectiveness ratios of <$100 000 per prevented DALY, with the cash transfer being more effective in the short term and the CSA being equally cost-effective in the long term, highlighting cost savings to society of −$191 100 per DALY averted (95% CI, −191 767 to −188 919) for the cash intervention and −$93 182 per DALY averted (95% CI, −93 707 to −92 503) for the CSA intervention. 132…”
Section: Nutritionmentioning
confidence: 99%
“…MSMs were initially populated by a sample of theoretical (synthetic) individuals using population distributions' parameters of demographics and risk factors (including diet) taken either from observational prospective cohort studies [as applied in (17,41,42)] or, more frequently, from population-representative health surveys, often combined with census statistics [as applied in (16,(43)(44)(45)(46)(47)(48)]. This sample of individuals-the starting cohort-was either drawn by taking a weighted sample of individuals included in the cohorts/surveys or was created by generating a "closeto-reality" synthetic population (Table 2).…”
Section: Formulation Of the Starting Cohortmentioning
confidence: 99%
“…In all studies, synthetic individuals entering the MSM acquired individualized risk factor trajectories, simulated using age and time trends from survey data, and that determined the associated individualized health transition rules. For all studies identified, a dynamic MSM based on discrete time was used; hence, individuals in the MSM were simulated to experience particular events in cycles with a length of either 1 day (40) (20,22,23,26,28,30,39,42,(44)(45)(46). The daily, monthly, or annually based risks and the associated transition probabilities for the onset of the NCDs of interest were estimated from either a multi-state life table approach, a hazard calculation approach, a risk score framework, or a CRA framework (Table 2).…”
Section: Individual Risks (And Associated Transition Rules)mentioning
confidence: 99%
“…In an example of a cash-benchmarking study, a recent trial sought to improve diet quality among patients at a community health center who were overweight or obese. 20,21 This study compared having a subsidized membership to a community-supported agriculture (CSA) program, which provided a weekly allotment of fresh produce, to receiving the cash value of the subsidy. The study found greater diet quality improvement in the CSA group, which showed that there was value to the program above and beyond the cash value of the subsidy.…”
Section: Cash Benchmarkingmentioning
confidence: 99%